Excessive crying due to erupting neonatal tooth: A case report - Mondal, Monojit; Biswas, Biswajit; Roy, Atanu; Kumar, Prashanth; Bose, Sayan; Biswas, Tanmoy; Banerji, Nayan; Rana, Kriti Sundar (Asian Journal of Medical Sciences, 2014)
Tooth eruption normally starts from 6 months of age. Teeth that appear at birth are called natal teeth, whereas, teeth that erupt during the first month of life are called neonatal teeth. Both are uncommon, with the ratio of natal to neonatal is 3:1. Presence of neonatal teeth may lead to complication in mother like painful bitten or bleeding nipples or it may cause complications in babies like difficulty in feeding, pain/distress due to erupting tooth, swallowing of the tooth, repeated trauma to the tip or undersurface of the tongue resulting in Riga-Fede ulceration and rarely aspiration. We are presenting a 15-day-old male baby who admitted at our hospital primarily with excessive crying and poor feeding and on a thorough physical examination revealed an erupting neonatal tooth. Other causes of excessive crying have been excluded. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11241 Asian Journal of Medical Sciences Vol.6(4) 2015 87-88